(untitled) (Research, Society and Development, 2023)
This study aimed to analyze the rhetorical argumentative strategies adopted by bars in Belo Horizonte during the COVID-19 pandemic on Instagram, aiming to understand the values and hierarchies adopted to attract and retain the public. The research adopted a qualitative approach, using content analysis of the posts published by the selected bars. Two bars in Belo Horizonte that maintained an active presence on Instagram during the pandemic were chosen. All posts from these bars between March and August 2022 were analyzed and categorized based on the rhetorical resources used and the values emphasized. Data analysis involved qualitative techniques, such as thematic content analysis and coding, and was based on theories of argumentative rhetoric and persuasive communication. The results revealed that the bars used communication strategies that highlighted humanitarian, affective, and solidary values, seeking to establish an emotional connection with the public. Values such as family, friendship, solidarity, respect, welcoming, and reliability were the most frequently used. These findings contribute to understanding the communication strategies adopted by bars during times of crisis and uncertainty. Understanding the values ​​and hierarchy employed by bars during the pandemic can provide valuable insights for developing communication strategies that establish an emotional connection with the public and promote a positive image of the company. In addition, these approaches can be applied in other sectors, providing a broader understanding of communication strategies used in challenging times.